2020
DOI: 10.22541/au.159410553.31991801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human-SARS-CoV-2 interactome and human genetic diversity: TMPRSS2-rs2070788, associated with severe influenza, and its population genetics caveats in Native Americans

Abstract: The current search for host-susceptibility variants for COVID-19 contrasts with the fact that the study of the genetic architecture of Severe Acute Respiratory Syndrome (SARS) has been neglected. For human/SARS-CoV-2 interactome genes ACE2, TMPRSS2 and BSG, there is only one convincing evidence of association in Asians with influenza-induced SARS for TMPRSS2-rs2070788, tag-SNP of the eQTL rs383510. This case illustrates the importance of population genetics and of sequencing data in the design of genetic assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…For the association study, we searched for the studies on TMPRSS2 gene variants reported in the literature elsewhere in relation to COVID-19 susceptibility ( Mollica et al, 2020 ; Andolfo et al, 2021 ; Asselta et al, 2020 ; Bhattacharyya et al, 2020 ; Darbani, 2020 ; Hou et al, 2020 ; Irham et al, 2020 ; Iyer et al, 2020 ; Jeon et al, 2020 ; Kim and Jeong, 2021 ; Latini et al, 2020 ; Paniri et al, 2021 ; Piva et al, 2021 ; Ragia and Manolopoulos, 2020 ; Senapati et al, 2020 ; Sharma et al, n.d. ; Singh et al, 2021 ; Strope et al, 2020 ; Torre-Fuentes et al, 2021 ; Vargas-Alarcón et al, 2020 ; Wang et al, 2020 ; Wulandari et al, 2021 ; Saih et al, 2021 ; Schönfelder et al, 2021 ; Kehdy et al, 2021 ) from this a total of 5 SNPs (rs2070788, rs734056, rs12329760, rs2276205, and rs3787950) was observed in our data and studied subsequently in detail. Data from the Estonian Biocentre ( Chaubey et al, 2017 ; Pathak et al, 2018 ; Re3data, 2014 ; Tätte et al, 2019 ), phase 3 of the 1000 Genomes Project ( Durbin et al, 2010 ), and our new genotyped samples from several Indian states were used to calculate the frequency of each of these SNPs among various Indian populations using plink 1.9.…”
Section: Methodssupporting
confidence: 60%
“…For the association study, we searched for the studies on TMPRSS2 gene variants reported in the literature elsewhere in relation to COVID-19 susceptibility ( Mollica et al, 2020 ; Andolfo et al, 2021 ; Asselta et al, 2020 ; Bhattacharyya et al, 2020 ; Darbani, 2020 ; Hou et al, 2020 ; Irham et al, 2020 ; Iyer et al, 2020 ; Jeon et al, 2020 ; Kim and Jeong, 2021 ; Latini et al, 2020 ; Paniri et al, 2021 ; Piva et al, 2021 ; Ragia and Manolopoulos, 2020 ; Senapati et al, 2020 ; Sharma et al, n.d. ; Singh et al, 2021 ; Strope et al, 2020 ; Torre-Fuentes et al, 2021 ; Vargas-Alarcón et al, 2020 ; Wang et al, 2020 ; Wulandari et al, 2021 ; Saih et al, 2021 ; Schönfelder et al, 2021 ; Kehdy et al, 2021 ) from this a total of 5 SNPs (rs2070788, rs734056, rs12329760, rs2276205, and rs3787950) was observed in our data and studied subsequently in detail. Data from the Estonian Biocentre ( Chaubey et al, 2017 ; Pathak et al, 2018 ; Re3data, 2014 ; Tätte et al, 2019 ), phase 3 of the 1000 Genomes Project ( Durbin et al, 2010 ), and our new genotyped samples from several Indian states were used to calculate the frequency of each of these SNPs among various Indian populations using plink 1.9.…”
Section: Methodssupporting
confidence: 60%